'Different, not less': pastoral care of autistic adults within Christian churches. Issue 3 (4th May 2021) - Burnett, Erin R.
ABSTRACT: The aim of this article is to reach a better understanding of how, with the correct support and pastoral care, autistic adults can fully partake as church members and serve in positions of leadership. There is a considerable gap in the literature regarding how churches should provide pastoral care for autistic adults, as most resources only focus on children; therefore, this paper endeavours to begin to fill the gap by listening to the experiences of autistic adults and synthesising their experience with relevant academic literature. Churches have a duty to follow the example of Christ, who took on human form and came alongside those who were ostracised from normative society, inviting them into the kingdom of God. In order to assist faith communities in fulfilling this calling, the study will produce a list of concrete, feasible and theologically justified actions that churches can implement with the aim of making churches more accessible for autistic adults.